2005
DOI: 10.2741/1704
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal function and alpha3 isoform of the Na/K-ATPase

Abstract: The Na/K-ATPase is a complex of integral membrane proteins that carries out active transport of sodium and potassium across the cell plasma membrane, and maintains chemical gradients of these ions. The alpha subunit of the Na/K-ATPase has several isoforms that are expressed in a cell type- and tissue-dependent manner. In adult vertebrates, while kidney cells express mostly alpha1, muscle and glial cells -- alpha1 and alpha2, and sperm cells -- alpha1 and alpha4 isoforms of Na/K-ATPase, neurons may express alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(133 citation statements)
references
References 212 publications
4
126
0
3
Order By: Relevance
“…With the exception of the neuron-specific ␣ 3 subunit, other isoforms are expressed in both neurons and glial cells (37, 46 -48). Even though there are cell-and region-specific differences in expression of various isoforms, many cell types in brain contain multiple Na,KATPase subunit isoforms (9,37,46). Accordingly, co-expression of the ␣ 1 , ␣ 2 , and ␤ 2 subunits in the same cells in rat brain cortex is detected here by immunofluorescence (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…With the exception of the neuron-specific ␣ 3 subunit, other isoforms are expressed in both neurons and glial cells (37, 46 -48). Even though there are cell-and region-specific differences in expression of various isoforms, many cell types in brain contain multiple Na,KATPase subunit isoforms (9,37,46). Accordingly, co-expression of the ␣ 1 , ␣ 2 , and ␤ 2 subunits in the same cells in rat brain cortex is detected here by immunofluorescence (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, other Na,K-ATPase subunit isoforms are expressed in a tissue-specific manner. The ␣ 2 isoform is expressed mainly in muscle and nervous system (1-3, 6, 7); the ␣ 3 isoform is expressed mainly in neurons (8,9), whereas the ␣ 4 isoform is found only in testis (10,11). The ␤ 2 isoform is expressed predominantly in brain and muscle (3,7), whereas the ␤ 3 isoform is mainly expressed in lung, testis, skeletal muscle, and liver (12,13).…”
mentioning
confidence: 99%
“…Thus, NKAα3 may be especially suited for the myelinated fiber types of the cochlea that sustain high rates of activity that would be expected to raise intracellular sodium concentrations, deplete ATP, and maintain hyperpolarized membrane potentials. In fact, the NKAα1 isoform, which has a much steeper voltage dependence of its transport rate compared to the NKAα3 isoform, may respond too quickly to action potential depolarization and prevent sustained firing (Dobretsov and Stimers 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ion and water transport in the brain are tightly regulated (48). The most studied role of the ␣ 3 isoform is its neuronal function, and failure of the Na ϩ /K ϩ -ATPase to maintain Na ϩ and K ϩ gradients leads to a decrease in both the RMP and the action potential and to altered neuronal excitability in several different neurons, such as rat hippocampus dentate interneurons, and pyramidal and Purkinje neurons (49). Consistent with this, we found that RB neurons had depolarized RMPs when Atp1a3a was knocked down.…”
Section: Discussionmentioning
confidence: 99%